Segmental vitiligo or frictional Koebner? - Bonifazi, E. (European Journal of Pediatric Dermatology, 2020)
The current case poses classification problems. The personal history begins with a halo nevus. The latter can be found in any type of vitiligo, but it can also be isolated. The shape of the white spot of the right buttock certainly indicates the elastic of the panty as a causative or localization factor: so we could speak of grade II Koebner phenomenon (KP) according to van Geel et Al. (2), that is due to friction with clothing; in some of these cases (1), like the current one, KP can have 3 colors (tricolor vitiligo). However, first of all the unilateral localization, although the frictional stimulus was bilateral, argues against this diagnosis; moreover, to talk about Koebner, there should be a pre-existing vitiligo and the latter should be extended and in the active phase (2). Thus monolaterality and lack of vitiligo in other sites favor the diagnosis of segmental vitiligo influenced by frictional stimulus.